1992
DOI: 10.1002/gps.930070503
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity among people aged 85+ in 1987. A follow‐up study at two and a half years: Associations with changes in psychiatric morbidity

Abstract: SUMMARYThis article reports findings from a longitudinal survey of very elderly people living at home in London. The research aimed to identify social, psychological and physical characteristics associated with positive ageing and successful survival in the community in later life and its converse-negative ageing-as well as the associated policy implications. Associations with psychiatric morbidity, measured using the General Health Questionnaire, among sample members without cognitive impairment between the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…The importance of maintaining and improving good levels of functioning in old age cannot be overemphasized. Previously reported analyses of depression among the baseline and follow-up respondents to this study show that decline in health and functional ability was the strongest predictor of baseline depression, and, after baseline depression, declining health in particular was predictive of worsening of depression over time (Bowling and Browne, 1991;Bowling and Farquhar, 1991;Bowling et al, 1992Bowling et al, , 1996. The consistency of these separate analyses with these datasets emphasizes the importance of early detection and timely rehabilitation.…”
Section: Discussionmentioning
confidence: 64%
“…The importance of maintaining and improving good levels of functioning in old age cannot be overemphasized. Previously reported analyses of depression among the baseline and follow-up respondents to this study show that decline in health and functional ability was the strongest predictor of baseline depression, and, after baseline depression, declining health in particular was predictive of worsening of depression over time (Bowling and Browne, 1991;Bowling and Farquhar, 1991;Bowling et al, 1992Bowling et al, , 1996. The consistency of these separate analyses with these datasets emphasizes the importance of early detection and timely rehabilitation.…”
Section: Discussionmentioning
confidence: 64%
“…There were no significant associations with GHQ score and marital status, household size and other network indicators, except that network size and structure (number of relatives and confidantes, and density) were significantly associated using chisquare test with change in GHQ score in the expected direction with the 85 plus sample; however, these variables were reduced to nonsignificance in a previous multiple regression analysis and are not re-presented here (Bowling et al, 1992).…”
Section: Resultsmentioning
confidence: 75%
“…The full baseline results, and some of the follow-up results for the 85 plus sample only, have been reported elsewhere (Bowling, 1990;Bowling and Farquhar, 1991;Bowling et a/., 1992). In previous baseline crosssectional analyses of the three samples of elderly people we found that 26% of the 85 plus inner city sample scored as a case using the General Health Questionnaire (GHQ), as did 10% of the inner city sample of people aged 65-75 and 21% of those aged 75-85; and 11% of the semi-rural sample of people aged 65-75 and 18% of those aged 65-75 scored as a case (Bowling and Farquhar, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher scores reflect elevated psychological distress. The scale has been shown to be valid and reliable: it correlates well with psychiatric diagnoses of morbidity and depression (Finlay-Jones & Murphy, 1979), and it has good construct validity (Berwick et al, 1987;Huppert & Garcia, 1991) and predictive validity (Bowling, Farquhar, Grundy, & Formby, 1992). Split-half reliability is acceptable, with a correlation of 0.95 reported in the literature (Bowling, 1997).…”
Section: Methodsmentioning
confidence: 96%